Global and domain-specific self-esteem after pediatric traumatic brain injury: Contribution of injury characteristics and parent mental health. Issue 8 (14th September 2022) - Khan, Noor; Ryan, Nicholas P.; Crossley, Louise; Hearps, Stephen; Catroppa, Cathy; Anderson, Vicki
ABSTRACT: This prospective, longitudinal case–control study examined global and domain-specific aspects of self-esteem 6-months following pediatric traumatic brain injury (TBI) and evaluated the contribution of injury-related factors and parent mental health to child self-esteem. Participants included 103 children with mild-severe TBI representing consecutive admissions to the emergency department of the Royal Children's Hospital, Melbourne, Australia. Forty-three age-and-sex matched typically developing controls were recruited for comparison. Information regarding injury characteristics including age at injury and clinical indicators of TBI severity were collected for participants at recruitment, with research magnetic resonance imaging conducted 2–8 weeks later. At 6 months post-injury, children rated their global and domain-specific self-esteem (Harter Self-Perception Profile for Children), and ratings of parent mental health were collected (General Health Questionnaire). Self-esteem for behavioural and academic domains was significantly poorer for children with TBI relative to TD children. In the TBI group, higher child-rated scores of global and domain-specific aspects of self-esteem were associated with more severe TBI, presence of frontal neuropathology, younger age at injury, and lower parental symptoms of anxiety/insomnia. Given the psychological status of parents represents a potentially modifiable risk factor, it may form the target of clinical interventions designed to bolster child self-esteem following pediatric TBI.